Green Dentistry: State of the Art and Possible Development Proposals - Stefano Speroni; Elisabetta Polizzi (Dentistry Journal)
Objectives: The objective of this narrative literature review was to highlight all dental procedures attributable to sectoral waste and to consider possible alternatives in line with the concept of sustainable development. Methods: An extensive search of electronic databases, including the Cochrane Oral Health Group Specialized Register, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, PubMed, EMBASE, and Google Scholar. Search words included ‘Green Dentistry’, ‘Dental Pollution’, ‘Pollutants and Dentistry’, ‘Disinfectants and Dentistry’, and ‘High-tech Dentistry’. All of them allowed an assessment of the impact of dental practice on the external environment, and new frontiers currently applied or possibly applicable for green dentistry were included in the study. Non-full-text papers, animal studies, studies in languages other than English, and studies not related to the topic under consideration were excluded. Results: According to the inclusion criteria, 76 papers were selected for the study. The topics analyzed were the impact of dental practice on the outdoor environment, currently applied and potentially applicable principles of green dentistry, and the ‘Four Rs’ model (Rethink, Reduce, Reuse, and Recycle). Conclusions: With the limitations of the present study, the concept of green dentistry could be applicable provided that the measures already taken to reduce indoor and outdoor risk factors are continued and improved.